Pharmacology of trifarotene. (1st August 2018) - Aubert, J.; Piwnica, D.; Bertino, B.; Blanchet‐Réthoré, S.; Carlavan, I.; Déret, S.; Dreno, B.; Gamboa, B.; Jomard, A.; Luzy, A.P.; Mauvais, P.; Mounier, C.; et al.
Summary: Acne is a chronic inflammatory skin disease, linked to changes in hormone levels. It mainly affects adolescents and young adults, and may lead to permanent scarring. 1.5 billion people aged between 15 and 45 suffer from some form of acne – mild, moderate or severe. Retinoic acid is one type of treatment for acne, and there are several different types, which are applied directly to the skin (topically). Trifarotene is a new type of retinoic acid which is able to act against only one particular retinoic acid receptor, and this study looked at whether it might be suitable for use in acne and other skin diseases, and potentially have an improved efficacy and safety profile compared with less selective retinoids (i.e. ones that target more than one retinoic acid receptor). Looking at the biological pathways of the drug, the authors suggest that it should be very effective in acne. Furthermore, trifarotene is expected to be rapidly eliminated in the blood stream, thereby potentially leading to fewer side effects and making it particularly useful for the treatment of large skin surface areas, such as the back and chest of acne patients. Based on these favourable characteristics of trifarotene, it is worth now investigating the clinical efficacy of this retinoid.